PENGARUH ECONOMIC VALUE ADDED (EVA), FINANCIAL VALUE ADDED (FVA), DAN MARKET VALUE ADDED (MVA) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB-SEKTOR JASA KONSUMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Pasimanyeku, Siti Masyitah I.; Muhsin N. Bailusy; Suratno Amiro (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of Economic Value Added (EVA), Financial Value Added (FVA), and Market Value Added (MVA) on financial performance. The population of this research consists of companies in the consumer services sub-sector listed on the IDX. The sample of this study includes 34 companies based on the following criteria: companies in the consumer services sub-sector listed on the IDX during the 2020–2022 period and companies that published complete and consecutive annual financial reports for 2020–2022. The results show that Economic Value Added (EVA) has a significant and negative effect on financial performance, Financial Value Added (FVA) has no effect on financial performance, and Market Value Added (MVA) has no effect on financial performance. Additionally, the simultaneous test results with a significance value of 0.000338 < 0.05 indicate that Economic Value Added (EVA), Financial Value Added (FVA), and Market Value Added (MVA) collectively have an effect on financial performance